Hubungan Sikap Dengan Kesiapsiagaan Tanggap Darurat Kebakaran Penghuni Gedung Di Rektorat Universitas Hasanuddin - Sudarman Sudarman (Jurnal Keperawatan Muhammadiyah, 2020)
Objective:  Office buildings that are  considered relatively safe, in reality faced with hazard potential such as fire.Methods:  The research used an analytic survey design with the cress sectional study approach. It involved 100 samples selected using the purposive sampling technique.Results:  The data were analysed statistically with chi-square thest shows that the result for the relationship between attitude and altertness is p=0.032 with α=0.05.Conclusion:  There is a relationship between attitude and alertness in terms of fire disaster emergency.